Material Evidence for Multiple Firings of Ancient Athenian Red‐Figure Pottery. Issue 7 (25th May 2013) - Walton, Marc; Trentelman, Karen; Cummings, Marvin; Poretti, Giulia; Maish, Jeff; Saunders, David; Foran, Brendan; Brodie, Miles; Mehta, Apurva; Vandiver, P.
<x xml:space="preserve">Abstract</x> The production of Athenian fine ware pottery, produced between the 6th and 4th centuries B.C., required alternating the high‐temperature kiln between oxidative and reductive environments during a single firing to create the iconic red and black decorative scenes. Here, we show that the production of this pottery was even more complex, with vessels subjected to two, or possibly more, firings in the kiln, with applications of slip between each firing. On a representative sherd, we compared three painted black decorative features—relief line, contour line, and background slip. Scanning transmission electron microscopy (STEM) of the slips revealed that the relief line had a more melted microstructure than either the contour line or background slip. By characterizing the chemistry and micromorphology of the slips, we find that the relief line microstructure could only be produced through a separate firing, at a hotter temperature, than the other two decorative features.